Delayed cerebral ischemia causing cortical blindness due to repeat cocaine use weeks subsequent to aneurysmal subarachnoid hemorrhage - Klein, Brendan J. (Radiol Case Rep, 2020)
Cocaine is a known vasoactive drug associated with poor clinical outcomes and high in-hospital mortality related to aneurysmal subarachnoid hemorrhage; however, the association of prior cocaine use with the incidence of vasospasm and delayed cerebral ischemia remains controversial. We report a case of a 42-year-old male with a history of active cocaine use who presented with a severe headache. Imaging demonstrated diffuse cisternal subarachnoid hemorrhage due to a ruptured basilar apex aneurysm, which was successfully treated with endovascular coil embolization. Despite expedited endovascular treatment and an initially benign clinical course, he suffered from delayed cerebral ischemia resulting in cortical blindness due to bilateral posterior cerebral artery vasospasm secondary to repeat cocaine use weeks after his initial ictus. To our knowledge, the present case is the first to describe delayed cerebral ischemia resulting in a severe neurologic deficit due to repeat cocaine use weeks subsequent to aneurysm rupture. We review the current literature on the association of cocaine use with the incidence of vasospasm and delayed cerebral ischemia as well as the effects of cocaine on the cerebrovasculature.